2004
DOI: 10.1038/sj.bjc.6601761
|View full text |Cite
|
Sign up to set email alerts
|

Survival results of a multicentre phase II study to evaluate D2 gastrectomy for gastric cancer

Abstract: Curative resection is the treatment of choice for potentially curable gastric cancer. Two major Western studies in the 1990s failed to show a benefit from D2 dissection. They showed extremely high postoperative mortality after D2 dissection, and were criticised for the potential inadequacy of the pretrial training in the new technique of D2 dissection, prior to the phase III studies being initiated. The inclusion of pancreatectomy and splenectomy in D2 dissection was associated with increased morbidity and mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(119 citation statements)
references
References 20 publications
8
104
1
6
Order By: Relevance
“…In the German gastric cancer study, a prognostic advantage of the D2-LAD was detected for the Union for International Cancer Control (UICC) stage II and IIIA disease [7,16]. Two recent prospective observational studies confirm the results of the non-randomized studies of the 1990s [28,29], and randomized studies from the Netherlands and the UK confirm earlier work that found lower rates of loco-regional recurrences after D2-LAD [30]. In two randomized trials with high proportions of splenectomy/pancreatectomy, a prognostic advantage after D2-LAD could not be detected [30,31].…”
Section: Surgerysupporting
confidence: 61%
“…In the German gastric cancer study, a prognostic advantage of the D2-LAD was detected for the Union for International Cancer Control (UICC) stage II and IIIA disease [7,16]. Two recent prospective observational studies confirm the results of the non-randomized studies of the 1990s [28,29], and randomized studies from the Netherlands and the UK confirm earlier work that found lower rates of loco-regional recurrences after D2-LAD [30]. In two randomized trials with high proportions of splenectomy/pancreatectomy, a prognostic advantage after D2-LAD could not be detected [30,31].…”
Section: Surgerysupporting
confidence: 61%
“…In europe and the UsA, D2 and more aggressive lymphadenectomies are not advocated, while D0 lymphadenectomy is thought to be insufficient; therefore, D1 lymphadenectomy is preferred (9,10). Previously, a phase II clinical trial of D2 resection by the Italian gastric cancer study group showed a morbidity rate of 20.9% and a postoperative mortality rate of 3.0%, which are similar to the rates for D1 dissections in both the Dgcg (7) and Mrc (8) trials, suggesting that D2 lymphadenectomy results in fewer complications in european as well as in Asian countries (11).…”
Section: Surgery For Gastric Cancermentioning
confidence: 81%
“…Nodal involvement in gastric cancer depends on the depth of cancer infiltration across the layers of the stomach (TNM staging): it occurs in 2-18% of T1 and in about 50% of T2 tumours. The surgical treatment of gastric cancer, in particular concerning the extent of LN dissection, varies among centres, but in many countries, for example Italy and Germany, the standard approach includes first and second level lymphadenectomy, independent of the evidence of LN metastases or the depth of cancer infiltration [3,4]. This means that in many patients lymphadenectomy is performed unnecessarily.…”
Section: Introductionmentioning
confidence: 99%